The challenges of primary health care in Amazonas and proposals for improving health care: an integrative literature review (Research, Society and Development, 2021)
Introduction: Primary care is defined as a set of health actions that encompass individual, family and collective actions involving health promotion, protection and recovery, becoming a Family Health Program or Family Health Strategy, seeking and effective care model in health. Objective: to present the challenges faced by the Family health strategy program. Methodology: This study is an integrated literature review, carried out from January 10, 2021 to February 21,2021, in the following databases: Lilacs, Pubmed, Scielo, Medline. Results and discussion: It was identified in the analyzed articles the diversity of tasks and action of the teams or workers of the Family Health strategy, in addition to the challenges encountered, demonstrated by the factors experienced by professionals in the reality of municipalities in the state of Amazonas. Final Considerations: Departing from the geographic and socioeconomic characteristics focused on the peculiarities and way of life of the population, primary care in Amazonas faces diversities regarding a limited resource scenario. Therefore, such factors require greater investment and training for professionals, in addition to conducting research focused on the subject, in order to clarify the impasses found and generate knowledge on the subject.